PENGARUH CITRA MEREK DAN PENGETAHUAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN ULANG AIR MINERAL CLEO DI ALFAMIDI KOTA PALU - DESI, DESI (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2017)
This study aims to determine the effect of brand image and product knowledge on the decision to repurchase mineral water CLEO in Alfamidi Jl. Martadinata Palu City. The independent variables used in this research are Company Image (X1), User Image (X2), Product Image (X3), Product Knowledge (X4), while the dependent variable is the repurchase decision (Y). This type of research is quantitative. The method of this research is descriptive causal. The sample used in this research is as much as 75 respondents with the form of sampling using purposive sampling technique. Data analysis method used in this research is multiple linear regression analysis method. The results of this study indicate that simultaneously the simultaneous influence of brand image and product knowledge consisting of corporate image, user image, and product image significantly influence against the decision of CLEO Mineral Water Buyback in Alfamidi. and partially corporate image, user image, product image, product knowledge significantly influence to decision of re-purchase of mineral water CLEO in Alfamidi Jl. Martadinata Palu City.